Registration of ‘UAM15‑2157‑4’ cowpea cultivar combining high yield and market demand traits for the savanna regions of West Africa - Omoigui, L.O.; Ekeruo, G.; Shaibu, A.S.; Kamara, A.Y.; Iorlamen, T.; Olufajo, O.O.; Eseigbe, O.B.; Solomon, R.; Ugbaa, M.S.; Timko, M.P. (2025)
In West Africa, cowpea [Vigna unguiculata (L.) Walp]. is an important food and source of nutrition for millions of people and feed for livestock. Grain yields are, however, very low due to low adoption of improved cultivars. Breeding efforts are being focused on developing new cultivars that align with both farmers′ and consumers′ preferences. UAM15-2157-4 (Reg. No. NGVU-25-44) was developed to address the problem of low adoption of existing improved cultivars. It was developed through a single backcross involving a landrace, ‘Oloyin’ and an improved line UAM09-1051-1. It is a high-yielding, medium-maturing cowpea cultivar with an indeterminate growth habit. It was developed and released in 2025 by the Cowpea Breeding Program of the Joseph Sarwuan Tarka University (JOSTUM), formerly the University of Agriculture Makurdi (UAM), in collaboration with the International Institute of Tropical Agriculture (IITA). This cultivar was released because of its high grain yield, large seed size, resistance to Striga, and adaptability to intercropping. It also shows tolerance to Fusarium wilt and bacterial blight and is well-adapted to the Northern and Southern Guinea savanna regions of West Africa. On average, UAM15-2157-4 had a mean grain yield of 1671 kg ha−1, representing a 56.7% higher yield advantage over the mean of the standard check (IT08K-150-12). The cultivar was approved for release and registered in the Nigeria Variety Catalogue of the Plant Varieties in 2025 with the national code FUAMPEA 5, also known as ALKAM SUPER, based on its superior performance in on-station, multi-location, and on-farm trials. The release of this cowpea cultivar, which has a high grain yield and desirable traits that meet the huge demand by farmers and consumers, will significantly contribute to transforming Nigeria’s agri-food systems.